A titanium-based bipolar plate for a fuel cell and a method for preparing the same
By adding conductive plasma on the bipolar plates of titanium -based materials, the problem of poor conductive performance of the bipolar boards of the titanium -based materials is solved, and it is realized on the basis of retaining corrosion resistance and met the demand for fuel cell piles. And has the advantages of low cost and efficient production.
Patent Information
- Application Number
- CN202310081328.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-02-08
AI Technical Summary
The bipolar plates prepared from existing titanium-based materials have poor conductivity and are difficult to meet the needs of fuel cell stacks.
The conductive filler and the conductive medium are uniformly mixed to form a conductive slurry, and the conductive slurry is added to the titanium-based metal bipolar plate body under high temperature conditions to form a titanium-based bipolar plate for the fuel cell. The method includes adding conductive slurry by deposition or coating under heating conditions of 300°C to 800°C in an amount of 30 μg/cm2 to 2000 μg/cm2.
The prepared titanium-based bipolar plate has good electrical conductivity while retaining good corrosion resistance, and can meet the use needs of fuel cell stacks. The preparation method is simple, the production cost is low, and the production efficiency is high. Suitable for batch or mass production.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a titanium-based bipolar plate for a fuel cell and a preparation method thereof. Background Art
[0002] A fuel cell is a device that generates electricity by chemically converting fuel and oxygen. Its structure mainly includes components such as bipolar plates, membrane electrodes and end plates. Among them, bipolar plates are the core components of the fuel cell structure. The main types include pure graphite bipolar plates, metal bipolar plates and composite bipolar plates.
[0003] Common metal bipolar plates can generally be made of titanium-based materials. Under the action of oxygen, the surface of titanium-based materials can form a variety of titanium-based oxide films with different titanium / oxygen ratios and a variety of different structures. The oxide film mainly contains TiO 2 Due to the presence of titanium-based oxide film, titanium-based materials have good corrosion resistance. However, the conductivity of titanium-based oxide film and titanium-based materials is poor, which easily affects the conductivity of bipolar plates, making the conductivity of bipolar plates poor and difficult to meet the use requirements of fuel cell stacks. Summary of the invention
[0004] Based on this, the present invention provides a titanium-based bipolar plate for fuel cells and a preparation method thereof, aiming to solve the problems that the bipolar plates prepared from existing titanium-based materials have poor electrical conductivity and are difficult to meet the needs of fuel cell stacks. The plate prepared in the present application has good electrical conductivity while retaining good corrosion resistance, and can meet the needs of fuel cell stacks.
[0005] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a titanium-based bipolar plate for a fuel cell, comprising the following steps:
[0006] S01, mixing a conductive filler and a conductive dielectric uniformly to obtain a conductive slurry; the mass ratio of the conductive filler to the conductive dielectric is 1:3-3:1;
[0007] S02, adding the conductive slurry of step S01 into an alcohol solvent, stirring evenly, to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate at 300°C-800°C to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 30 μg / cm 2 -2000μg / cm 2 .
[0008] As a preferred embodiment, in step S01,
[0009] The conductive filler is one of nano carbon black, carbon fiber, nano carbon tube and graphene, or a mixture of at least two of them.
[0010] The conductive medium is a viscous substance or a mixture of a viscous substance and metal particles.
[0011] The adhesive is one of phenolic resin (PF), epoxy resin (EP), polyimide (PI), polyvinylidene fluoride (PVDF), polyether sulfone (PES) and polyetherimide (PEI) or a mixture of at least two of them.
[0012] The metal particles are metal alloys.
[0013] The metal alloy is one or a mixture of at least two of silver, aluminum, copper and gold.
[0014] As a preferred embodiment, in step S02,
[0015] The alcohol solvent is ethanol.
[0016] The mass fraction of carbon contained in the conductive slurry is 1%-6%.
[0017] Preferably, the conductive slurry further contains an oxygen-rich material, and the mass of the oxygen-rich material is 1%-5% of the mass of the conductive slurry.
[0018] The oxygen-rich material is preferably NaClO 3 , hydrogen peroxide, water and potassium permanganate, or a mixture of at least two of them.
[0019] The addition is achieved by direct coating or deposition.
[0020] The thickness of the titanium-based metal bipolar plate is 0.05 mm to 1 mm.
[0021] The titanium-based metal bipolar plate body is preferably pretreated by the following method: removing the oxide film of the titanium-based metal bipolar plate body to obtain a pretreated titanium-based metal bipolar plate body.
[0022] The removal is achieved by pickling, plasma bombardment, polishing or grinding.
[0023] When the conductive slurry contains an oxygen-rich material, the adding is performed in a vacuum, and the oxygen partial pressure of the vacuum is 0.0001Pa-0.01Pa.
[0024] When the conductive slurry does not contain oxygen-rich material, the adding is performed during oxygen circulation supply, and the oxygen partial pressure of the oxygen circulation supply is 0.2Pa-20Pa.
[0025] The titanium-based metal bipolar plate body is a titanium-based metal bipolar plate body with molded flow channels or a titanium-based metal bipolar plate body without molded flow channels.
[0026] On the other hand, the embodiments of the present application also provide a titanium-based bipolar plate for a fuel cell obtained by the above-mentioned preparation method.
[0027] This application can solve the problem that the bipolar plates made of existing titanium-based materials have poor electrical conductivity and are difficult to meet the use requirements of fuel cell stacks. The plates prepared by this application have good electrical conductivity while retaining good corrosion resistance, which can meet the use requirements of fuel cell stacks. The preparation method of the present invention is simple, has low production cost, high production efficiency, and is easy to batch or large-scale production.
[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0031] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0032] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0033] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0034] Generally, under the action of oxygen, the surface of titanium-based materials can form a variety of titanium-based oxide films with different titanium / oxygen ratios and a variety of different structures. The oxide film mainly contains TiO 2 Due to the presence of titanium-based oxide film, titanium-based materials have good corrosion resistance. However, the conductivity of titanium-based oxide film and titanium-based materials is poor, which easily affects the conductivity of bipolar plates, making the conductivity of bipolar plates poor and difficult to meet the use needs of fuel cell stacks. Based on this, it is necessary to provide a fuel cell titanium-based bipolar plate and a preparation method thereof to solve the above technical problems.
[0035] In the present application, a conductive slurry (the components of the conductive slurry and their usage ratio are controlled) is added to the surface of the titanium-based metal bipolar plate. The conductive medium in the conductive slurry can be combined and connected with the titanium-based material of the titanium-based metal bipolar plate, so that the conductive performance of the prepared fuel cell titanium-based bipolar plate is greatly enhanced.
[0036] Under heating conditions, oxygen will re-oxidize the titanium on the surface of the titanium-based metal bipolar plate from which the oxide film has been removed into a new titanium-based oxide film. The new titanium-based oxide film will cover the portion of the conductive medium that is not connected to the titanium-based material of the titanium-based metal bipolar plate and other parts of the conductive medium. The corrosion resistance of the resulting fuel cell titanium-based bipolar plate decreases less or even does not decrease compared to the untreated titanium-based metal bipolar plate, and still retains good corrosion resistance.
[0037] To achieve the above objectives, on the one hand, an embodiment of the present invention provides a method for preparing a titanium-based bipolar plate for a fuel cell, comprising the following steps:
[0038] S01. Evenly mix a conductive filler and a conductive dielectric to obtain a conductive paste; the mass ratio of the conductive filler to the conductive dielectric is 1:3-3:1 (e.g., 1:3, or 1:1, or 2:1, or 3:1, etc.);
[0039] S02, adding the conductive slurry of step S01 into an alcohol solvent, stirring evenly, to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate at 300°C-800°C (e.g., 300°C, 500°C, 600°C, 800°C, etc.), to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 30 μg / cm 2 -2000μg / cm 2 (For example, it can be 30 μg / cm 2 , or 500 μg / cm 2 , or 1000 μg / cm 2 , or 2000 μg / cm 2 etc).
[0040] As a preferred embodiment, in step S01,
[0041] The conductive filler is one of nano carbon black, carbon fiber, nano carbon tube and graphene or a mixture of at least two of them. The conductive filler can be selected according to actual use requirements.
[0042] The conductive medium is a viscous substance or a mixture of a viscous substance and metal particles.
[0043] The adhesive is one of phenolic resin, epoxy resin, polyimide, polyvinylidene fluoride, polyether sulfone and polyetherimide, or a mixture of at least two of them. The adhesive can be selected according to actual use requirements.
[0044] The metal particles are metal alloys.
[0045] The metal alloy is one or a mixture of at least two of silver, aluminum, copper and gold.
[0046] As a preferred embodiment, in step S02,
[0047] The alcohol solvent is ethanol.
[0048] The conductive slurry contains carbon (here, carbon refers to the carbon element) in a mass fraction of 1%-6% (eg, 1%, or 3%, or 5%, or 6%, etc.).
[0049] Preferably, the conductive slurry further contains an oxygen-rich material, and the mass of the oxygen-rich material is 1%-5% (eg, 1%, 3%, 4%, 5%, etc.) of the mass of the conductive slurry.
[0050] The oxygen-rich material is preferably NaClO 3 , hydrogen peroxide, water and potassium permanganate, or a mixture of at least two of them.
[0051] The addition is achieved by direct coating or deposition.
[0052] The thickness of the titanium-based metal bipolar plate is 0.05 mm to 1 mm. The thickness of the plate can be selected according to actual needs, such as 0.05 mm, 0.07 mm, 1 mm, etc.
[0053] The titanium-based metal bipolar plate body is preferably pretreated by the following method: removing the oxide film of the titanium-based metal bipolar plate body to obtain a pretreated titanium-based metal bipolar plate body.
[0054] The removal is achieved by pickling, plasma bombardment, polishing or grinding.
[0055] When the conductive slurry contains an oxygen-rich material, the addition is performed in a vacuum, and the oxygen partial pressure of the vacuum is 0.0001Pa-0.01Pa (e.g., it may be 0.0001Pa, or 0.001Pa, or 0.009Pa, or 0.01Pa, etc.). Since the oxygen-rich material in the conductive slurry releases oxygen, under vacuum heating conditions, the released oxygen will re-oxidize the titanium on the surface of the titanium-based material metal bipolar plate from which the oxide film has been removed into a new titanium-based oxide film, and the new titanium-based oxide film will cover at least a portion of the conductive slurry.
[0056] When the conductive slurry does not contain oxygen-rich material, the addition is performed in the oxygen circulation supply, and the oxygen partial pressure of the oxygen circulation supply is 0.2Pa-20Pa (such as 0.2Pa, or 1Pa, or 10Pa, or 20Pa, etc.). Under heating conditions, the oxygen released in the oxygen supply environment will re-oxidize the titanium on the surface of the titanium-based material metal bipolar plate from which the oxide film has been removed into a new titanium-based oxide film, and the new titanium-based oxide film will cover at least a portion of the conductive slurry.
[0057] The titanium-based metal bipolar plate body is a titanium-based metal bipolar plate body with molded flow channels or a titanium-based metal bipolar plate body without molded flow channels.
[0058] Under high temperature conditions, Ti will react with O 2 Oxidation reaction occurs to generate TiO 2 :Ti+O 2 =TiO 2 .
[0059] The flexural strength of the titanium-based bipolar plate for the fuel cell is preferably 20 MPa-80 MPa, and the conductivity is preferably 200 S / cm-600 S / cm.
[0060] The thinnest thickness of the titanium-based bipolar plate for the fuel cell is preferably 0.05 mm to 0.1 mm, and can be 0.05 mm, or 0.07 mm, or 1 mm, etc.
[0061] On the other hand, the embodiments of the present application also provide a titanium-based bipolar plate for a fuel cell obtained by the above-mentioned preparation method.
[0062] This application can solve the problem that the bipolar plates made of existing titanium-based materials have poor electrical conductivity and are difficult to meet the use requirements of fuel cell stacks. The plates prepared by this application have good electrical conductivity while retaining good corrosion resistance, which can meet the use requirements of fuel cell stacks. The preparation method of the present invention is simple, has low production cost, high production efficiency, and is easy to batch or large-scale production.
[0063] Example 1
[0064] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0065] S01, mixing nano carbon black and phenolic resin in a mass ratio of 1:1 to obtain a conductive paste;
[0066] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 600° C. and a vacuum degree of 0.01 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 500 μg / cm 2 ; The deposition time is 20min.
[0067] The conductive slurry contains 1% carbon by mass; the conductive slurry also contains an oxygen-rich material NaClO 3 , the mass of the oxygen-rich material is 1% of the mass of the conductive slurry.
[0068] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 80 MPa and a conductivity of 600 S / cm;
[0069] The thinnest thickness of the titanium-based metal bipolar plate with molded flow channels is 0.1 mm;
[0070] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 3mΩ·cm 2 , the corrosion current density is 0.9μA·cm -2 .
[0071] Example 2
[0072] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0073] S01, mixing nano carbon black and polyimide resin in a mass ratio of 1:1 to obtain a conductive paste;
[0074] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 500° C. and an oxygen partial pressure of 20 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 50 μg / cm 2 ; The deposition time is 30min.
[0075] The conductive slurry contains carbon in a mass fraction of 1%.
[0076] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 80 MPa and a conductivity of 600 S / cm;
[0077] The thinnest thickness of the titanium-based metal bipolar plate with molded flow channels is 0.1 mm;
[0078] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 5mΩ·cm 2 , the corrosion current density is 0.82μA·cm -2 .
[0079] Example 3
[0080] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0081] S01, mixing a conductive filler and a phenolic resin in a mass ratio of 1:2 to obtain a conductive paste; wherein the conductive filler is a mixture of carbon nanotubes and graphene in a mass ratio of 0.4:0.6;
[0082] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 800° C. and a vacuum degree of 0.01 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 1000 μg / cm 2 ; The deposition time is 20min.
[0083] The conductive slurry contains 1% carbon by mass; the conductive slurry also contains an oxygen-rich material NaClO 3, the mass of the oxygen-rich material is 1% of the mass of the conductive slurry.
[0084] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 60 MPa and a conductivity of 500 S / cm;
[0085] The thinnest thickness of the titanium-based metal bipolar plate with molded flow channels is 0.05mm;
[0086] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2mΩ·cm 2 , the corrosion current density is 0.80μA·cm -2 .
[0087] Example 4
[0088] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0089] S01, mixing a conductive filler and a polyimide resin in a mass ratio of 1:2 to obtain a conductive paste; wherein the conductive filler is a mixture of carbon nanotubes and graphene in a mass ratio of 0.6:0.4;
[0090] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 800°C and an oxygen partial pressure of 10 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 100 μg / cm 2 ; The deposition time is 30min.
[0091] The conductive slurry contains carbon in a mass fraction of 1%.
[0092] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 60 MPa and a conductivity of 500 S / cm;
[0093] The thinnest thickness of the titanium-based metal bipolar plate with molded flow channels is 0.05mm;
[0094] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2mΩ·cm 2 , the corrosion current density is 0.79μA·cm -2 .
[0095] Example 5
[0096] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0097] S01, mixing nano carbon black and a conductive medium in a mass ratio of 1:3 to obtain a conductive slurry;
[0098] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.7:0.3;
[0099] The viscous material is a mixture of phenolic resin and polyvinylidene fluoride, wherein the mass content of the phenolic resin is 60% and the mass content of the polyvinylidene fluoride is 40%; the metal particles are silver-tungsten alloy;
[0100] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.05 mm thick) by coating at 500° C. and a vacuum degree of 0.005 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 2000 μg / cm 2 ; The coating time is 20min;
[0101] The conductive slurry contains carbon at a mass fraction of 1%. The conductive slurry also contains an oxygen-rich material, hydrogen peroxide, and the mass of the oxygen-rich material is 3% of the mass of the conductive slurry.
[0102] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 20 MPa and a conductivity of 200 S / cm;
[0103] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2mΩ·cm 2 , the corrosion current density is 0.79μA·cm -2 .
[0104] Example 6
[0105] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0106] S01, mixing the conductive filler and the conductive medium in a mass ratio of 3:1 to obtain a conductive slurry;
[0107] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.7:0.3;
[0108] The sticky substance is a mixture of epoxy resin, polyethersulfone and polyetherimide, wherein the mass content of phenolic resin is 50%, the mass content of polyvinylidene fluoride is 30% and the mass content of polyetherimide is 20%;
[0109] The metal particles are silver-copper-vanadium alloy.
[0110] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.5 mm thick) by coating at 300° C. and a vacuum degree of 0.001 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 500 μg / cm 2 ; The coating time is 20 minutes.
[0111] The conductive slurry contains carbon at a mass fraction of 1%. The conductive slurry also contains an oxygen-rich material, potassium permanganate, and the mass of the oxygen-rich material is 2% of the mass of the conductive slurry.
[0112] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 80 MPa and a conductivity of 600 S / cm;
[0113] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2.5 mΩ·cm 2 , the corrosion current density is 0.81μA·cm -2 .
[0114] Example 7
[0115] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0116] S01, mixing nano carbon black and a conductive medium in a mass ratio of 1:3 to obtain a conductive slurry;
[0117] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.7:0.3;
[0118] The viscous material is a mixture of phenolic resin and polyvinylidene fluoride, wherein the mass content of the phenolic resin is 60% and the mass content of the polyvinylidene fluoride is 40%;
[0119] The metal particles are silver-tungsten alloy.
[0120] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.05 mm thick) by coating at 500° C. and an oxygen partial pressure of 15 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 2000 μg / cm 2 ; The coating time is 20 minutes.
[0121] The conductive slurry contains carbon in a mass fraction of 1%.
[0122] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 20 MPa and a conductivity of 200 S / cm;
[0123] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2.7 mΩ·cm 2 , the corrosion current density is 0.83μA·cm -2 .
[0124] Example 8
[0125] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0126] S01, mixing the conductive filler and the conductive medium in a mass ratio of 3:1 to obtain a conductive slurry;
[0127] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.7:0.3;
[0128] The sticky substance is a mixture of epoxy resin, polyethersulfone and polyetherimide, wherein the mass content of phenolic resin is 50%, the mass content of polyvinylidene fluoride is 30% and the mass content of polyetherimide is 20%;
[0129] The metal particles are silver-copper-vanadium alloy.
[0130] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.5 mm thick) by coating at 300° C. and an oxygen partial pressure of 10 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 500 μg / cm 2 ; The coating time is 20 minutes.
[0131] The conductive slurry contains carbon in a mass fraction of 1%.
[0132] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 80 MPa and a conductivity of 600 S / cm;
[0133] The contact resistance of the prepared titanium-based bipolar plate for fuel cells was 3.1 mΩ·cm. 2 , the corrosion current density is 0.86μA·cm -2 .
[0134] Example 9
[0135] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0136] S01, mixing nano carbon black and a conductive medium in a mass ratio of 1:3 to obtain a conductive slurry;
[0137] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.3:0.7;
[0138] The viscous material is a mixture of phenolic resin and polyvinylidene fluoride, wherein the mass content of the phenolic resin is 60% and the mass content of the polyvinylidene fluoride is 40%;
[0139] The metal particles are aluminum-manganese alloy.
[0140] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 500° C. and an oxygen partial pressure of 0.2 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 30 μg / cm 2 ; The deposition time is 30min.
[0141] The conductive slurry contains carbon in a mass fraction of 1%.
[0142] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 20 MPa and a conductivity of 200 S / cm;
[0143] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 3mΩ·cm 2 , the corrosion current density is 0.81μA·cm -2 .
[0144] Example 10
[0145] A method for preparing a titanium-based bipolar plate for a fuel cell comprises the following steps:
[0146] S01, mixing nano carbon black and a conductive medium in a mass ratio of 1:3 to obtain a conductive slurry;
[0147] The conductive medium is a mixture of viscous matter and metal particles, and the mass ratio of the viscous matter to the metal particles is 0.3:0.7;
[0148] The adhesive is a mixture of epoxy resin and polyvinylidene fluoride, wherein the mass content of phenolic resin is 60% and the mass content of polyvinylidene fluoride is 40%;
[0149] The metal particles are silver-cadmium oxide.
[0150] S02, adding the conductive slurry of step S01 into ethanol and stirring evenly to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate (0.1 mm thick) by deposition at 500° C. and an oxygen partial pressure of 20 Pa to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 30 μg / cm 2 ; The deposition time is 30min.
[0151] The conductive slurry contains carbon in a mass fraction of 1%.
[0152] In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels, and the titanium-based metal bipolar plate with molded flow channels has a bending strength of 20 MPa and a conductivity of 200 S / cm;
[0153] After testing, the contact resistance of the prepared titanium-based bipolar plate for fuel cells is 2mΩ·cm 2 , the corrosion current density is 0.83μA·cm -2 .
[0154] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a titanium-based bipolar plate for a fuel cell, characterized in that: The steps include: S01, mixing a conductive filler and a conductive dielectric uniformly to obtain a conductive slurry; the mass ratio of the conductive filler to the conductive dielectric is 1:3-3:1; S02, adding the conductive slurry of step S01 into an alcohol solvent, stirring evenly, to obtain a conductive slurry; adding the conductive slurry to a titanium-based metal bipolar plate at 300°C-800°C to obtain a fuel cell titanium-based bipolar plate; the amount of the conductive slurry added is 30 μg / cm 2 -2000μg / cm 2 ; The conductive filler is one or a mixture of at least two of nano carbon black, carbon fiber, nano carbon tube and graphene; The conductive medium is a viscous substance or a mixture of a viscous substance and metal particles; When the conductive slurry contains an oxygen-rich material, the adding is performed in a vacuum, and the oxygen partial pressure of the vacuum is 0.0001Pa-0.01Pa; When the conductive slurry does not contain an oxygen-rich material, the adding is performed during oxygen circulation supply, and the oxygen partial pressure of the oxygen circulation supply is 0.2 Pa-20 Pa.
2. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 1, characterized in that: The adhesive is one or a mixture of at least two of phenolic resin, epoxy resin, polyimide, polyvinylidene fluoride, polyether sulfone and polyetherimide; The metal particles are metal alloys.
3. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 1, characterized in that: In step S02, the alcohol solvent is ethanol; and the mass fraction of carbon contained in the conductive slurry is 1%-6%.
4. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 1, characterized in that: In step S02, the conductive slurry further contains an oxygen-rich material, and the mass of the oxygen-rich material is 1%-5% of the mass of the conductive slurry.
5. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 4, characterized in that: The oxygen-rich material is one or a mixture of at least two of NaClO3, hydrogen peroxide, water and potassium permanganate; The adding is achieved by direct coating or deposition; The thickness of the titanium-based metal bipolar plate is 0.05 mm-1 mm.
6. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 1, characterized in that: In step S02, the titanium-based metal bipolar plate is a titanium-based metal bipolar plate with molded flow channels or a titanium-based metal bipolar plate without molded flow channels.
7. The method for preparing a titanium-based bipolar plate for a fuel cell according to claim 1, characterized in that: In step S02, the bending strength of the titanium-based bipolar plate of the fuel cell is 20MPa-80MPa, and the conductivity is 200 S / cm-600 S / cm; The thinnest thickness of the titanium-based bipolar plate of the fuel cell is 0.05 mm to 0.1 mm.
8. A titanium-based bipolar plate for a fuel cell, characterized in that: The fuel cell titanium-based bipolar plate is prepared by the preparation method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Bipolar plate for electrochemical cells and method for the production thereof
CN107210456A
Metal-based composite bipolar plate substrate with low contact resistance and preparation method thereof
CN110137524A